Dual Task Training Interventions and Mobility-Based Outcomes in Children with Cerebral Palsy: A Scoping Review. - Rubsam, Meaghan; Girolami, Gay L.; Bhatt, Tanvi (Physical & Occupational Therapy in Pediatrics, 2025)
Purpose: Children with cerebral palsy (CP) struggle in dual task (DT) situations, where interference may decrease performance when executing two simultaneous tasks. Dual task training (DTT) improves primary motor performance in individuals with typical development and neurological conditions, and emerging research also suggests benefits for DT performance. Its potential in children with CP, however, remains unexplored. This scoping review aims to (1) identify; (2) describe; and (3) synthesize the current evidence for DTT interventions in children with CP, and (4) evaluating its effects on mobility-based impairment, activity, and participation level outcomes. Methods: Five electronic databases were searched. Studies were included if they were in English, included children with CP, used a motor-motor or motor-cognitive DTT intervention, detailed the intervention, and reported results. Results: The six studies included 117 children with CP (F: 50, M: 67) and used motor-motor (n = 2) and motor-cognitive (n = 4) DTT paradigms. Training ranged from 480 to 1800 min, and all studies showed improved primary motor task performance. Conclusion: Despite the study heterogeneity, the results provide early, yet promising, evidence that DTT may enhance primary motor task performance in children with CP. Robust and rigorous research is needed to explore the effects of exercise prescription, training regimens, and optimal dosing on motor and cognitive outcomes.